Incidencia de la tecnología agrícola ecuatoriana en el sector de la producción agrícola durante el período 1990 – 2019 - Robles Saritama, Edinson Francisco (2024)
In this research it is revealed that in different countries the economy depends on agricultural and manufacturing exports of agricultural origin and the adverse effects of climate change are a threat to their development; Latin America represents 13% of world agricultural and fishing production. In Ecuador, agricultural production represents 7.7% of the total GDP (Gross Domestic Product). For this reason, it is suggested to obtain international technology to increase production which has not been adjusted to territorial and regional conditions, because these innovations have been delivered by developed countries. The general objective of the research is to carry out an analysis of the incidence of technological implementation on agricultural production in Ecuador during the period 1990-2019. From there it is important to note that the database has been taken from the World Bank and where it was necessary to apply descriptive, explanatory and correlated statistics, an ARDL model (autoregressive model with distributed lags) was used, allowing to verify their relationship in the long run. term, as well as a Granger causality model, to determine the causal relationship. Given this, the main findings show that there is evidence that correlates agricultural production and technological implementation. Therefore, the ARDL model allowed us to demonstrate the existence of a long-term relationship between the study variables. Likewise, the Granger causality test provided evidence of a causal relationship between some variables used for this study. Leaving as results that technological implementation is inefficient for Ecuadorian agricultural production, due to technological backwardness and poor use of technological packages, where policies must be oriented to the use of new technological packages that respect the environment and maintain the organic soil nutrients